2020
DOI: 10.2147/jmdh.s259151
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Applicability of the Patient-Specific Functional Scale (PSFS) in Rehabilitation for Patients with Acquired Brain Injury (ABI) – A Cohort Study</p>

Abstract: Aim: The primary aim of this study was to investigate the applicability of the Patient-Specific Functional Scale (PSFS) in patients with acquired brain injury (ABI) admitted to a specialized rehabilitation unit in a regional hospital. A secondary aim was to identify patient characteristics and functioning that predicted changes in the PSFS. Patients and Methods: In a cohort study, 59 patients with ABI were assessed for the ability to complete the PSFS. A trained multidisciplinary team applied the PSFS as part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The Target Outcomes approach also includes a severity rating by the respondents, enabling assessment of change posttreatment relevant for both research and clinical practice purposes. Another outcome measure based on patient-reported difficulties recently shown to be applicable in a population of acquired brain injury 48 is the Patient Specific Functional Scale (PSFS). 49 However, the PSFS is activity-based whereas the Target Outcomes approach allows for the identification of a broader range of problems.…”
Section: Discussionmentioning
confidence: 99%
“…The Target Outcomes approach also includes a severity rating by the respondents, enabling assessment of change posttreatment relevant for both research and clinical practice purposes. Another outcome measure based on patient-reported difficulties recently shown to be applicable in a population of acquired brain injury 48 is the Patient Specific Functional Scale (PSFS). 49 However, the PSFS is activity-based whereas the Target Outcomes approach allows for the identification of a broader range of problems.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, self-report measures that can be easily adapted and interpreted by the stroke survivor need to be prioritised. The Patient Specific Functional Scale (PSFS) is one such measure, which is currently being investigated for use in this population (Evensen et al, 2020). Use of the PSFS allows stroke survivors to set their own goals and to revise their goals as and when their goals or circumstances change.…”
Section: Discussionmentioning
confidence: 99%
“…Another study involving patients with subacute stroke showed that 8% of the sample who were unable to complete the PSFS had severe cognitive or language impairment. 20 Nevertheless, health professionals should exercise caution when using PSFS results to guide decision-making when patients have poor cognitive function or language difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…The authors stated that the PSFS might be appropriate to administer but concluded that there were gaps in the literature regarding its measurement properties for these populations. Evensen et al 20 investigated the applicability of the PSFS in patients with acquired brain injury (92% with stroke) and concluded that 92% (n = 54) could complete the PSFS. The patients who could not complete the PSFS (n = 5) demonstrated severe cognitive or language impairment.…”
Section: Introductionmentioning
confidence: 99%